CD19-Targeted CAR T Cells as Novel Cancer Immunotherapy for Relapsed or Refractory B-Cell Acute Lymphoblastic Leukemia - Davila, Marco L. (Clin Adv Hematol Oncol, 2016)
Immunotherapy has demonstrated significant potential for the treatment of patients with chemotherapy-resistant hematologic malignancies and solid tumors. One type of immunotherapy involves the adoptive transfer of T cells that have been genetically modified with a chimeric antigen receptor (CAR) to target a tumor. These hybrid proteins are composed of the antigen-binding domains of an antibody fused to T-cell receptor signaling machinery. CAR T cells that target CD19 recently have made the jump from the laboratory to the clinic, and the results have been remarkable. CD19-targeted CAR T cells have induced complete remissions of disease in up to 90% of patients with relapsed or refractory B-cell acute lymphoblastic leukemia (B-ALL), who have an expected complete response rate of 30% in response to chemotherapy. The high efficacy of CAR T cells in B-ALL suggests that regulatory approval of this therapy for this routinely fatal leukemia is on the horizon. We review the preclinical development of CAR T cells and their early clinical application for lymphoma. We also provide a comprehensive analysis of the use of CAR T cells in patients with B-ALL. In addition, we discuss the unique toxicities associated with this therapy and the management schemes that have been developed.